Cerebral Palsy: Parental Stress of Caregivers - Lima,Mayara Barbosa Sindeaux (2021)
Abstract The aim of this research was to investigate indicators of parental stress among caregivers of children with Cerebral Palsy. The study covered a total of 132 participants who responded to the following instruments: Sociodemographic Inventory, Gross Motor Function Classification System, and Parental Stress Index (PSI). Data were analyzed using descriptive statistics. The sample was composed mainly of mothers (97%); most of the children were classified under the most severe levels of motor impairment (61%). Regarding the PSI, almost half of the sample experienced high levels of parental stress (46.2%). The PSI domain with the highest percentage of caregivers with high stress was Parental Distress (60.6%). Most caregivers prioritize the needs of the child with Cerebral Palsy over their own needs more than they expected (90%). These results may support intervention strategies aimed at minimizing parental stress.